Episomal and integrative DNA transformation in Candida albicans using frozen EZ Yeast transformation kit II - Ahmad, Hasna; Ramzi, Ahmad Bazli; Arzmi, Mohd Hafiz (IIUM Press, 2019)
C. albicans is an important opportunistic fungus that is virulent in immunocompromised individuals such as HIV, cancer or transplant patients. Transformation of C. albicans is fundamental to genetic manipulation of C. albicans since it lacks a complete sexual cycle. Homologous recombination is the predominant method for transformation and expression of exogenous DNA, however, the expression of episomal plasmids have been reported. Genetic transformation of C. albicans is traditionally done via lithium acetate/spheroplast/electoporation methods that are time- consuming and/or complicated. The Frozen EZ Yeast Transformation II kit is a fast, broad spectrum, high transformation efficiency method for preparing competent cells and performing multiple plasmid transformations in yeast cells. The kit allows for easier and more efficient yeast circular and linear plasmid transformations compared to protocols. However, its effectiveness in C. albicans has not been reported. Here we report transformation of circular episomal DNA and linear integrative DNA into C. albicans using the Frozen EZ Yeast Transformation II kit. Heat shock at 44 °C, overnight incubation and outgrowth step were added as modifications specific to C. albicans transformation to increase transformation efficiency using the kit. The results with and without modification to the general kit protocol were compared. Transformation efficiency of episomal DNA using the general kit protocol was 40%, while for linear DNA, transformation did not occur. Addition of C. albicans- specific steps to the transformation protocol increased transformation efficiency. In conclusion, the Frozen EZ Yeast Transformation II kit is suitable for C. albicans transformation of circular DNA. Addition of C. albicans-specific modification steps increases transformation efficiency of C. albicans using the kit.